SOCIAL AND ETHICAL PRINCIPLES OF ORGANIC AGRICULTURE - Антонець, С. С.; Антонець, А. С.; Лук’яненко, Т. В.; Писаренко, П. В.; Писаренко, В. М.; Писаренко, В. В. (Scientific Progress & Innovations, 2013)
The results of research of the expediency of replacement the agrochemical concept of agriculture for agrobiological were uttered. The organic farming, where the production philosophy is caring for the ground, obtaining ecologically safe food products, which is one of the main factors of human health, is subservient to this to the greatest extent.